Is Ozonation Treatment Efficient to Provide Safe Reclaimed Water? Assessing the Effects of Synthetic Wastewater Effluents in Human Cell Models - Ana Teresa Rocha; Fátima Jesus; Helena Oliveira; João Gomes; Joana Luísa Pereira (Applied Sciences)
Ozonation has been promoted as a successful methodology for recovering effluents from wastewater treatment plants, with special emphasis on wastewater contaminated with pharmaceutical and personal care products (PPCPs). Still, ozonation reactions may generate potentially toxic by-products, jeopardizing human health safety, a critical aspect considering the use of reclaimed water. We aimed at understanding the potential impacts of ozonation on the quality of reclaimed water for human use through cell viability assays with human skin keratinocytes (HaCaT cell line). Under this context, the cytotoxicity of synthetic effluents contaminated with methyl- and propylparaben, paracetamol, sulfamethoxazole, and carbamazepine, both individually and in mixtures, was assessed before and after ozonation. The viability of HaCaT cells decreased after exposure to untreated synthetic effluents, denoting the cytotoxicity of the tested PPCPs singly and more prominently in mixtures (especially in those combining two and three PPCPs). A similar pattern was observed when testing effluents treated with ozonation. Since the parent contaminants were fully removed during ozonation, the observed cytotoxicity relates to degradation by-products and interactive effects among them. This study suggests that ozonation is poorly efficient in reducing cytotoxicity, as required for the safe use of ozone-treated reclaimed water in activities involving direct contact with human skin.